The emergence of new antigen branches of H9N2 avian influenza virus in China due to antigenic drift on hemagglutinin through antibody escape at immunodominant sites - Nan Zhang; Keji Quan; Zixuan Chen; Qun Hu; Maoshun Nie; Nuo Xu; Ruyi Gao; Xiaoquan Wang; Tao Qin; Sujuan Chen; Daxin Peng; Xiufan Liu (Emerging Microbes and Infections)
Vaccination is a crucial prevention and control measure against H9N2 avian influenza viruses (AIVs) that threaten poultry production and public health. However, H9N2 AIVs in China undergo continuous antigenic drift of hemagglutinin (HA) under antibody pressure, leading to the emergence of immune escape variants. In this study, we investigated the molecular basis of the current widespread antigenic drift of H9N2 AIVs. Specifically, the most prevalent h9.4.2.5-lineage in China was divided into two antigenic branches based on monoclonal antibody (mAb) hemagglutination inhibition (HI) profiling analysis, and 12 antibody escape residues were identified as molecular markers of these two branches. The 12 escape residues were mapped to antigenic sites A, B, and E (H3 was used as the reference). Among these, eight residues primarily increased 3`SLN preference and contributed to antigenicity drift, and four of the eight residues at sites A and B were positively selected. Moreover, the analysis of H9N2 strains over time and space has revealed the emergence of a new antigenic branch in China since 2015, which has replaced the previous branch. However, the old antigenic branch recirculated to several regions after 2018. Collectively, this study provides a theoretical basis for understanding the molecular mechanisms of antigenic drift and for developing vaccine candidates that contest with the current antigenicity of H9N2 AIVs.